2019
DOI: 10.3389/fmicb.2019.02677
|View full text |Cite
|
Sign up to set email alerts
|

Ni(II) Interactions in Boreal Paenibacillus sp., Methylobacterium sp., Paraburkholderia sp., and Pseudomonas sp. Strains Isolated From an Acidic, Ombrotrophic Bog

Abstract: The uptake of nickel [Ni(II)] by Paenibacillus sp., Methylobacterium sp., Paraburkholderia sp., and Pseudomonas sp. strains isolated from a boreal bog was studied using batch experiments. All strains removed Ni(II) from the solution and the uptake efficiency was affected by the nutrient source, incubation temperature, time, and pH. As highest Ni uptake (with a maximum Kd of 1890 L/kg DW) was recorded for the Pseudomonas sp. strains, these bacteria were used in the following protein expression (SDS-PAGE and MAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Commercially available peat has successfully been used as sorbent for the removal of Ni from aqueous solutions [125], indicating that the peat itself may sorb the Ni and perhaps that is why there is a specific layer where the Ni appears to be enriched in the peat profile. Nevertheless, bacterial strains originating from Lastensuo have been shown to accumulate Ni intracellularly as well as by sorption to cell surfaces [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially available peat has successfully been used as sorbent for the removal of Ni from aqueous solutions [125], indicating that the peat itself may sorb the Ni and perhaps that is why there is a specific layer where the Ni appears to be enriched in the peat profile. Nevertheless, bacterial strains originating from Lastensuo have been shown to accumulate Ni intracellularly as well as by sorption to cell surfaces [23].…”
Section: Discussionmentioning
confidence: 99%
“…Retardation may occur through cell surface metal-binding functional groups, like carboxyl, hydroxyl, phosphate, and sulfate groups [18][19][20]. In addition, many microbes are able to accumulate Ni also inside the cells (see, e.g., in [22]) and until this date at least two different uptake mechanisms have been reported: ATP-binding cassette (ABCtype) transporters as well as Ni-specific permeases [23]. The possible toxic effects of Ni may be suppressed during active accumulation inside bacterial cells through detoxification reactions and previously we observed that Ni(II) concentrations between 0.01 and 1 mM had no toxic effects on Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…for its potential in biotechnological applications ( Jimoh and Lin, 2019 ; Du et al, 2021 ). To this date, some studies on the interactions of Paenibacillus strains with metals have been produced ( Knuutinen et al, 2019 ; Ogunyemi et al, 2020 ) but only a few concerning Te ( Chien and Han, 2009 ). Strains of Paenibacillus have been characterized for their biochemistry and proteomics and considered of interest in rhizostabilization of cadmium ( Kumari and Thakur, 2018 ) for their high metal resistance, siderophore production, biocontrol activities, and xenobiotic degradation.…”
Section: Introductionmentioning
confidence: 99%